PROGRAM PENGEMBANGAN BUDAYA KEWIRAUSAHAAN BAGI MAHASISWA PERGURUAN TINGGI MELALUI KETERAMPILAN PERCETAKAN - Rubiyanto, Rubino (WARTA, 2007)
Untill predominate out-comes of the CollegeÂ  are job seeker.Â  TochangeÂ  the mind setÂ  them to become the job creator presumably need aneffort, stock purchasing andÂ  giving of capital entrepreneur. Therefore noits bad if the student FKIP to made as a professional teacher candidate,also given entrepreneur lecturer.Â  This lecturer is programmed in anpackage: KWU in the field of offset printing skill. Target of this activity is:(a) develop the culture of entrepreneur in PT, (b) the student have thestock of science and skill of offset printing area, (c) student have theknowledgeÂ  about trick of the trade, developing idea of effort, managingeffort, marketing strategy and obtain;get the capital employed, (d)student have the readiness of business. The target of this activity are 30studentâs of FKIP in semester VI from various program. Lecturing methodcover the discourse, discussion, duty, question and answer, compilationof proposal business, seminar proposal, simulation and also practice inprinting office. Resistance met by execution KWU at the same time bylecturer fundamental so that execution entrepreneur delayed. Finally theenterpreur program areÂ  executedÂ  after even semester test 2006 finishing.Activity exterior for example; 1) piled up over by module entrepreneur,vision of business mission, career tuition, credit system of this effort; 2)piled up over by proposal business in group; 3) the expectedÂ  after studentpass, 25 % participant earn the entrepreneur offset printing.